Gestational age-specific weight gain based on the indices of the American institute of medicine in the second and third trimester of pregnancy and its related factors - Mahin Kiyani Mask; Maryam Aradmehr; Elham Azmoude (Tehran University of Medical Sciences, 2020)
Background & Aim: Optimal weight gain during pregnancy, as an important indicator of maternal and fetal health, is affected by many adjustable variables. The present study was conducted to evaluate the gestational age-specific weight gain based on the indices of the American Institute of Medicine and to determine its related factors. Methods & Materials: In this descriptive study, 250 pregnant women referred to the health centers of Torbat Heydarieh were assessed in 2018. The gestational age-specific weight gain was calculated for each woman, and based on the amount of deviation from the IOM indices, the subjects were divided into three groups including weight gain less than optimal, optimal and over than optimal. Data collection tools were demographic questionnaire and Multidimensional Body Relationship Questionnaire. Data were analyzed by chi-square, ANOVA, Kruskal-Wallis tests and ordinal regression using the SPSS software version 16. Results: In this study, 22% of the subjects gained weight less than optimal, 46.4% gained weight normally and 31.6% had excessive weight gain. Weight gain in most women with normal and low body mass index was in a normal range (55.4%) and in most overweight and obese women was higher than an optimal range (43.2% and 35.7%, respectively). Weight gain was related to age, education, parity, abortion history, feelings of women and their partners toward pregnancy and wanting the pregnancy from the viewpoint of the partner (P<0.05). After entering the significant variables into the ordinal regression model, only nulliparity was able to predict pregnancy weight gain status (P=0.017). Conclusion: Optimal weight gain in most pregnant women of this study may reflect the proper nutrition and effectiveness of prenatal care in this city. Identifying factors related to weight gain out-of-range increases the effectiveness of interventions on weight gain.